(untitled) (Altre Modernità, 2012)
The case of Sesto San Giovanni (SSG), a town marked by a previously intense industrial development then into an equally fast decline of production, may show effectively the impact of the urban regeneration, with the implied redesign of landscape and land policies. The whole process of gradual dismissal of manufacturing, the dynamics of industrial restructuring and the urban processes of recovery, reuse, reclamation and enhancement are triggering a wide debate among geographers and in other fields of research. Being probably the most complex product of human civilization, the city is obviously the most sophisticated and clarifying subject for territorial, social, economical, anthropological, linguistic and cultural studies. As a territorial framework, it is difficult to conceive globally: its boundaries are unstable, and its shapes tend to change very quickly. SSG entered the twenty-first century as a "visible city", a place where its dwellers, old and new, may find at the same time the marks of history and the signs of urban regeneration. However, SSG is also an “invisible city”, soaked with a symbolic heritage that requires protection, preservation and enhancement. Precisely for this reason the municipality decided to apply for UNESCO’s support, in order to protect its industrial heritage. Symbols, signs and values, at the same time, may prove a great resource to be moulded and exploited in terms of major events such as the International Expo scheduled for 2015, which could prove a great opportunity for the city.